Modeling and analysis of split-Pi converter using State space averaging technique - Singhai M.; Pilli N.; Singh S.K. (My University, 2025)
Potential of bidirectional Split-Pi converter is yet to be exploited. Its unique features like bidirectional property, option to employ in multiphase systems and smaller ratings of passive elements provides liberty to use it in applications demanding high power density such as in hybrid electric vehicles, renewable energy, aerospace, military etc. In this paper dynamic model of Split-Pi converter is presented. State space averaging technique is used to derive the transfer function of Split-Pi converter operating in boost mode and type II compensator is designed for the stable closed loop operation of the converter. All the simulations of the converter are done using LTspice simulation software. © 2014 IEEE.